Pengaruh Kompensasi, dan Lingkungan Pekerjaan Terhadap Turnover Intentions melalui Kepuasan Kerja di PT Akasha Wira International - Lambok Hasian Joanne Olivia; Rivera Pantro Sukma (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2023)
This research was conducted to determine and prove the effect of compensation and the work environment on turnover intentions through employee job satisfaction at PT Akasha Wira International Tbk. The population in this study are employees of PT Akasha Wira International Tbk. The sampling technique used saturated sampling of 205 respondents. Methods of data collection using questionnaires distributed to respondents. Meanwhile, hypothesis testing includes path analysis with the help of SmartPLS 3.0. The results of this study are that the direct effect of compensation has no significant effect on job satisfaction, compensation has no significant effect on turnover intentions, the work environment has a positive and significant effect on turnover intentions and job satisfaction has a significant positive effect on turnover intentions and for the indirect effect of compensation has no significant effect on turnover intentions through job satisfaction, while the work environment has a significant positive effect on turnover intentions through job satisfaction. The result of the coefficient of determination on job satisfaction is 33.6% and turnover intentions are 55.9%.